Development of a Droplet Digital™ PCR DNA methylation detection and quantification assay of prenatal tobacco exposure - Katti Arroyo; Anahit Nargizyan; Francianne G Andrade; Swe Swe Myint; Sabrina Lu; Priyatama Pandey; Amy Yee; Adam J de Smith; Joseph L Wiemels (BioTechniques, 2022)
DNA methylation is a labile modification associated with gene expression control and environmental adaptations. High throughput, scalable and quantitative assessments of specific DNA methylation modifications in complex genomic regions for use in large population studies are needed. The performance of Droplet Digital™ PCR (ddPCR™) was investigated for DNA methylation detection against next-generation bisulfite sequencing (NGS) to demonstrate the ability of ddPCR to detect and validate DNA methylation levels and complex patterns among neighboring CpGs in regions associated with prenatal tobacco exposure. While both techniques are reproducible, ddPCR demonstrates a unique advantage for high-throughput DNA methylation analysis in large-scale population studies and provides the specificity to accurately measure DNA methylation of target CpGs in complex regions.